2018
DOI: 10.1016/j.infsof.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Feature location benchmark for extractive software product line adoption research using realistic and synthetic Eclipse variants

Abstract: Context: It is common belief that high impact research in software reuse requires assessment in non-trivial, comparable, and reproducible settings. However, software artefacts and common representations are usually unavailable. Also, establishing a representative ground truth is a challenging and debatable subject. Feature location in the context of software families, which is key for software product line adoption, is a research field that is becoming more mature with a high proliferation of techniques. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…As shown by Martinez et al [16], feature location in the extractive approach of SPLE can be illustrated by the Fig. 1.…”
Section: Feature Location For Software Product Line Reengineeringmentioning
confidence: 93%
See 2 more Smart Citations
“…As shown by Martinez et al [16], feature location in the extractive approach of SPLE can be illustrated by the Fig. 1.…”
Section: Feature Location For Software Product Line Reengineeringmentioning
confidence: 93%
“…None of these feature location techniques consider the changes of refactorings. There are a number of benchmarks [16,15,6] that have been used to evaluate FL techniques performance [5,24,18], while we used one of them to estimate the performance of FL techniques with refactored variants. We have previously presented the ArgoUML SPL benchmark, which have been used to evaluate many FL techniques [5,18,19].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our empirical analysis showed that features have been changed over time by adding or removing an entire file and/or fewer lines. The information retrieved from the mapping between artifacts and features in relation to the relevant information was compared by measuring precision, recall, and F1 score, which are metrics commonly used to evaluate feature location techniques [5,21,23]. In summary, we achieved higher precision and recall for information retrieved from the systems' variants, ranging from 99%-100% and 93%-99%, respectively, at filelevel and line-level granularity.…”
Section: Evaluating the Efficiency Of A Technique For Locating Featurmentioning
confidence: 95%
“…Another FL research used crowd-based screen cast to help programmers find a sample of code from video tutorial [2]. Many others were used information retrieval (IR) to discover FL within a source code [3]; [4][5][6][7]. Most of its used Java-based code as data sets of their experiment.…”
Section: Introductionmentioning
confidence: 99%